Wheat Production and Consumption Gap: A Case Study of Baluchistan Province - Imam Ud din Palal (Corresponding Author); Muhammad Zohaib; Shahab Khan; Ali Mustafa; Nisar Ahmed Jokhio (`, 2025)
Wheat is the most widely grown cereal crop worldwide, supplying nearly 20% of global dietary calories and protein, and thus plays a critical role in international food security. In Pakistan, wheat contributes more than 60% of daily caloric intake and is indispensable for household and national food stability. Within this context, Baluchistan, the country’s largest but sparsely populated province faces a persistent wheat production and consumption imbalance. to evaluate whether Balochistan’s wheat production meets its consumption requirements, identify high-yielding districts, and propose policy measures to narrow the gap, This study uses secondary data from the Pakistan Bureau of Statistics (PBS, 2022), Crop Reporting Services Baluchistan (CRSB, 2022), and international agricultural databases to estimate provincial wheat supply and demand. Results indicate that Balochistan’s annual requirement was 1.85 million tonnes (based on the per capita benchmark of 124 kg/year), while production was only 1.52 million tonnes, creating a deficit of 0.33 million tonnes. Per capita availability stood at 102 kg, significantly below the national average and global standards. District-level analysis highlights Naseerabad and Jaffarabad as relatively high-yielding areas, whereas rain-fed districts remain constrained by scarce irrigation and climate variability. The province’s reliance on inter-provincial transfers, coupled with post-harvest losses, underscores its vulnerability to food insecurity. Strengthening irrigation systems, adopting climate-resilient varieties, improving storage infrastructure, and reducing post-harvest losses are essential to bridging the production consumption gap and ensuring sustainable food security in Baluchistan. Keywords: Wheat production, consumption gap, Baluchistan food security, climate resilience